P1 2 Green Shell Launch Velocity In Mario Kart - Kelly, Claire; Blase, Lucy; Blue, Rane; Thompson, Jack (Physics Special Topics, 2023)
This paper investigates the required launch velocity for a green shell to cause various characters’ karts to spin-out as shown in Mario Kart gameplay. By modelling the three karts as squares of different sizes and using their moment of inertia combined with the conservation of kinetic energy, the shell velocity could be calculated. To make two full rotations in one second for Toad, Yoshi, and Bowser this was found to be 24.2 ms−1 , 57.2 ms−1 , and 221.3 ms−1 respectively.